Poligami di Malaysia dan Indonesia Serta Relevansinya dengan Pemenuhan Hak Gender - Pradikta, Hervin Yoki; Muhammad, Hasanuddin; Asmara, Musda (Institut Agama Islam Negeri Curup, 2020)
This paper aims to find out the provisions of polygamy in Malaysia and Indonesia related to the protection and fulfillment of wife's rights from a gender perspective. The method of writing this article uses a comparison, by comparing the provisions of polygamy in the two countries then analyzing it with a gender approach. The result is that both countries allow polygamy. However, the provisions on the permissibility of practicing polygamy in Malaysia and Indonesia place more emphasis on physical conditions. Such as reasons because they are barren, aged, crazy and cannot serve and carry out their obligations as a wife. The ability of polygamy prioritizes the fulfillment of the husband's rights by providing solutions for channeling the husband's sexual desire. Whereas in the historical context, polygamy was carried out on the grounds of religious preaching and protection of widows and orphans. This provision is a form of injustice and discrimination against wives. The wife in a weak position has no choice and is the victim of these regulations. For this reason, it is necessary to add polygamy permissibility requirements where the prospective wife to be married is a widow who has orphans.